French for refugee service providers - Whitehead, Shelley (French Language and Literature, 2015)
This dissertation entitled French for Refugee Service Providers, aims to provide a curriculum for teaching French as a Foreign Language to those working with French-speaking refugees in South Africa. Firstly, the context of the project is thoroughly discussed, which substantiates the importance of language for the integration of refugees into the host country. Specific attention is given to the South African situation. This study then provides a review of the literature outlining the most pertinent issues with regards to the domain of teaching French as a Foreign Language (TFFL) and French for Specific Purposes (FSP). Finally, the process as well as the results of a needs analysis conducted amongst a sample of people working with refugees in Durban, South Africa are presented in detail. Based on these results, a curriculum for teaching French to refugee service providers is suggested, together with examples of three lesson plans and two evaluation activities.